A Comprehensive Literature Review of Implications of Preoperative Depression for Lumbar Spine Surgery Outcomes - Arief, Arief; Rizki Kurnia, Rizki Kurnia; Catherine, Catherine (International Medical Journal Corp. Ltd, 2024)
Background: The literature reviewed emphasizes the significant impact of preoperative depression on surgical outcomes for patients undergoing lumbar spine surgery. The studies collectively highlight a consistent link between depressive symptoms and adverse postoperative results, suggesting that psychological health is a critical factor influencing recovery trajectories. Literature Review: The foundational study by (Sinikallio et al., 2010) provides compelling evidence that both preoperative and postoperative depressive symptoms predict poor surgical outcomes. This research underscores the importance of mental health not only before surgery but also during the rehabilitation process, indicating that ongoing depressive symptoms can exacerbate recovery challenges. Further expanding on this theme, (L. Jackson et al., 2019) conducted a systematic review that connects psychological comorbidities with postoperative complications. Their work reveals that preoperative depression correlates with increased rates of delirium, readmissions, and prolonged hospital stays, suggesting that elevated cortisol levels in depressed individuals may be a contributing factor to these adverse outcomes. Additionally, the retrospective study by (Zhang et al., 2023) specifically examines the effects of preoperative depression on outcomes following cervical laminoplasty, providing valuable insights that can be extrapolated to lumbar spine surgeries. Conclusion: In conclusion, the literature consistently demonstrates that preoperative depression is a significant predictor of surgical outcomes in lumbar spine surgery. The integration of psychological assessments into preoperative evaluations is essential for optimizing patient care and enhancing recovery trajectories. Addressing mental health prior to surgery could mitigate adverse outcomes and improve overall patient well-being, highlighting the need for targeted interventions in this population.